Menjaga Kesucian Seksual di Era Modern: Integritas Spiritual Remaja - Herman, Samuel (LOGIA: Jurnal Teologi Pentakosta, 2023)
This study explores the dynamics of moral issues among adolescents with a focus on sexual integrity. Using a literature review approach, the research discusses the key roles of spiritual, moral, and emotional maturity, as well as the application of religious values in understanding and maintaining sexual integrity. The analysis of Joseph's life in Genesis 39 highlights that integrity is not limited by external situations but is closely related to the foundation of individual maturity. The conclusion emphasizes the crucial role of parents, teachers, and spiritual leaders in guiding the younger generation towards sexual integrity. The foundation of this maturity needs to be integrated into adolescent education to shape individuals who are moral, resilient, and capable of facing the challenges of the times.